The effect of absorptive capacity on the financial performance of Brazilian and Portuguese companies in a low technological intensity sector - Juliane Laviniki; Claudionor Guedes Laimer; Carlos Rodrigues; João Lourenço Marques (BBR: Brazilian Business Review)
The digital transformation has driven a more assertive absorption of external information and knowledge in all economic activities, especially in the low technological intensity sector, where competition has been fierce. In this way, the use of information and knowledge can provide companies with higher performance before its competitors. Thus, this study seeks to verify the effect of absorptive capacity (ACAP) on the financial performance of Brazilian and Portuguese companies that operate in low technological intensity sectors. The study is part of initial research that addresses ACAP in sectors that do not release innovations in the market. A survey was carried out based on validated scales, but adapted to the low technology sector. Then, a new validation of the scales was carried out and a t-test was performed to check if there are differences and regression analysis to answer the hypotheses. The results showed that ACAP has an effect on financial performance, both in the Brazilian and Portuguese context, being higher in Portuguese companies. In addition, it was also shown that the two dimensions of ACAP have different influences on financial performance, when considering the two contexts. It can be concluded that ACAP can be applied in sectors of low technological intensity, as this has an influence over the financial performance of companies.